2019
DOI: 10.3389/fphar.2019.00404
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Challenges of Post-traumatic Stress Disorder: Focus on the Dopaminergic System

Abstract: Post-traumatic stress disorder (PTSD) is a mental illness developed by vulnerable individuals exposed to life-threatening events. The pharmacological unresponsiveness displayed by the vast majority of PTSD patients has raised considerable interest in understanding the poorly known pathophysiological mechanisms underlying this disorder. Most studies in the field focused, so far, on noradrenergic mechanisms, because of their well-established role in either tuning arousal or in encoding emotional memories. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 115 publications
(132 reference statements)
0
21
0
Order By: Relevance
“…Stressful and traumatic events may trigger the development of 3 main different symptom clusters, such as intrusion (ie, flashbacks, repetitive intrusive memories, and distressing dreams), avoidance (ie, active attemps to not think and talk about the event), and hyperarousal (ie, exaggerated startle, sleep disturbance, hypervigilance, impulsivity, and aggressiveness). 10 We found that patients with PD with higher prelockdown levels of anxiety symptoms experienced more frequent thoughts about the lockdown (ie, higher IES-R intrusion subscale scores), found it more effortful not to think about the lockdown (ie, higher IES-R avoidance subscale scores), and felt more marked anger and irritability (ie, higher IES-R hyperarousal subscale scores). Dopaminergic as well as serotoninergic and adrenergic pathways have been involved in both anxiety symptoms in PD 37 and stress-related responses.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Stressful and traumatic events may trigger the development of 3 main different symptom clusters, such as intrusion (ie, flashbacks, repetitive intrusive memories, and distressing dreams), avoidance (ie, active attemps to not think and talk about the event), and hyperarousal (ie, exaggerated startle, sleep disturbance, hypervigilance, impulsivity, and aggressiveness). 10 We found that patients with PD with higher prelockdown levels of anxiety symptoms experienced more frequent thoughts about the lockdown (ie, higher IES-R intrusion subscale scores), found it more effortful not to think about the lockdown (ie, higher IES-R avoidance subscale scores), and felt more marked anger and irritability (ie, higher IES-R hyperarousal subscale scores). Dopaminergic as well as serotoninergic and adrenergic pathways have been involved in both anxiety symptoms in PD 37 and stress-related responses.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, there is compelling evidence linking impaired dopaminergic signaling and psychological posttraumatic stress. 10 Nigro-striatal dopamine depletion is the most relevant pathophysiological process in Parkinson's disease (PD). Other pathways, mainly serotoninergic, adrenergic, GABAergic, and cholinergic, also have been shown to play a role in the pathogenesis of motor and nonmotor symptoms in PD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PTSD is considered a major health challenge ( Shalev et al, 2017 ). The suicide risk associated with PTSD is very high ( Kessler, 2000 ) and available treatments with the selective serotonin reuptake inhibitors (SSRIs) paroxetine and sertraline, which are the only two medications approved by U.S. Food and Drug Administration (FDA), are unsatisfactory ( Malikowska-Racia and Salat, 2019 ; Torrisi et al, 2019 ). Thus, there is an urgent need to develop more effective treatments for PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…Finally. there is also evidence of an important role for dopamine in the pathophysiology of PTSD (Lee et al, 2017 ; Torrisi et al, 2019 ) with potential interaction with oxytocinergic systems (Zhang et al, 2019 ), further strengthening the suggestion about the potential usefulness of music therapy given the known impact that music has on dopaminergic motivation and reward systems in the human brain (Chanda and Levitin, 2013 ; Zatorre and Salimpoor, 2013 ; Ferreri et al, 2019 ).…”
Section: The Links Between Oxytocin and Musicmentioning
confidence: 99%